Electrochemical direct CO2 capture technology using redox-active organic molecules to achieve carbon-neutrality - Choi, Gwan Hyun; Song, Hyun Jun; Lee, Seolhwa; Kim, Jeong Yoon; Moon, Myoung-Woon; Yoo, Pil J. (Elsevier BV, 2023)
The global community has set an ambitious goal of achieving carbon neutrality by 2050. To achieve this goal, significant reductions in carbon dioxide emissions from human activities are required. Carbon capture tech-nology has been identified as a viable solution for addressing global energy depletion and mitigating the effects of fossil fuel consumption on climate change. Recent advances in carbon capture technique based on wet scrubbing have typically focused on increasing carbon capture efficiency. However, this approach requires extensive use of amine CO2 sorbents and high energy consumption for high temperature and pressure operation. An alternative approach is electrochemical direct carbon capture (EDCC), which allows for the capture of CO2 from diluted sources such as direct air capture (DAC) or direct ocean capture (DOC), ultimately resulting in net -zero carbon emissions. Therefore, it is crucial to design cost-effective and energy-efficient CO2 adsorbent mol-ecules for EDCC applications. In this review, we discuss recent advancements in EDCC technology and their potential for future applications, especially using organic active materials. We provide an overview of the fun-damentals of EDCC and practical strategies for demonstrating an EDCC system, including molecular design, electrolyte selection, and device configuration. We also delve into design strategies for potential redox-active organic sorbents, with a particular emphasis on understanding currently utilized material candidates from other electrochemical applications and density functional theory (DFT) calculation-guided material selection in the design principle of EDCC. In the final section, we present an opportunity for carbon neutrality utilizing electrochemically-mediated carbon capture technologies. We anticipate that approaches employing an appro-priate EDCC design will provide an innovative platform for high-performance and next-generation carbon cap-ture technologies and an opportunity for carbon neutrality.